MENINGKATKAN KINERJA KARYAWAN DENGAN PENINGKATAN MOTIVASI KERJA PADA BUNABABY CARE - Akbar, Rifal Nuari; Fitria, Ida Jalilah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This research aims to examine information in depth and be open to different answers and reveal their different thoughts regarding a topic regarding employee motivation and employee performance at Bunababy Care Spa. Motivation is measured based on several indicators such as responsibility, work performance, and challenging work which aims to encourage employees to achieve their organizational and individual goals. Meanwhile, employee performance is assessed based on work quality, punctuality of work and attendance. This research uses a qualitative descriptive research method to obtain information regarding employee motivation and performance at the BunaBaby care company. The data collected is the result of observations, interviews and documentation carried out by the author with 3 audiences, namely 2 midwives and 1 admin. The results of this research are that high work motivation, driven by responsibility, achievement, and job challenges that match abilities, plays an important role in improving employee performance at the Bunababy Care Spa Clinic. They demonstrate a commitment to maintaining high quality standards and managing time effectively to ensure the best service for the spa clinic's customers. It is hoped that the Bunababy Care Spa Clinic can increase employee motivation and overall performance